EFFECT OF FEED ACIDIFIERS ON PERFORMANCE OF BROILERS (Indian Journal of Animal Production and Management, 2014)
One hundred and eighty day-old broiler chicks were randomly distributed into four groups, each group having three replicates. Each replicate contained fifteen chicks. The treatments were T0 - control diet without acidifier prepared as per national standards (2005), T1 – control diet + feed acidifier acidlacdry @ 3 kg/t, T2 – control diet + acidlacdry @ 4 kg/t, T3 – control diet + acidlacdry @ 5 kg/t. The starter ration was offered upto three weeks and finisher ration thereafter upto six weeks of age. The body weights of broilers at 6th weeks of age were significantly higher in T3 (1893.80), T2 (1893.70) and T1 (1836.50) groups. The most efficient feed conversion ratio were observed in T3 (1.75), T2 (1.76) and T1 (1.80) treatment groups as compared to control. The carcass characteristics viz., dressing yield, drumstick yield, giblet yield and abdominal fat pad were not affected by treatments indicative of the fact that use of acidifiers doesn’t play any role in improving the carcass traits. However, the use of feed acidifier acidlacdry @ 3, 4 and 5 kg/t improved gut health and nutrient utilization resulting into improved production performance in broilers
Keywords: Broilers; acidifiers; ration; management; body weights; carcass